Literature why it matters - Eaglestone, Robert 1968- (Cambridge, UK Medford, MA Polity, 2019)
"Despite centuries of arguments, no one can agree on what literature is, or how to study it. But, argues Eaglestone, it is precisely the open-ended nature of literature that makes it such a rewarding and useful subject of study. Literature is a living conversation which provides endless opportunities to rethink and reinterpret our world"-- Provided by publisher.
What is literature? -- Studying literature -- Why does literature matter? -- What does literature teach?
Includes index.
Keywords: Literature -- History and criticism